Characteristics of driving self-assessments and factors related to inaccurate self-assessment in Japanese older adults. (September 2021) - Kosuge, Ritsu; Okamura, Kazuko; Nakano, Yukako; Fujita, Goro
Highlights: Japanese older drivers completed a questionnaire and an on-road driving assessment. Their self-assessments were shown to be inaccurate and exceed expert assessments. Inaccurate self-assessments were partly related to vehicle speed and entropy rate. Making older drivers recognize evaluative criteria may be effective for improving self-assessments. Improving self-assessments has the potential to improve driving behavior. Abstract: Older adults are considered to decide their driving behaviors based their own assessment of their driving performance, and thus it is important that these self-assessments be accurate. Therefore, this study aimed to clarify how older drivers assess their driving performance and examine factors related to the level of inaccuracy in their self-assessments. Japanese drivers aged 70 years or older (N = 181) were asked to assess their own driving performance by questionnaire and then to drive on a public road while wearing an electronic device that measured their actual driving behaviors. They were accompanied by a driving instructor who sat in the passenger seat and assessed their driving performance. The results showed that older drivers' self-assessments were significantly higher than the experts' assessments of their driving performance. This tendency applied to all driving competencies, including overall rating, speed, and scanning. In addition, there were greater discrepancies between self-assessments and expert assessments for drivers who were rated poorly by experts compared with those who were highly rated. Drivers with a greater rating discrepancy were likely to drive faster around an intersection with a stop sign. This discrepancy was also related to a low entropy rate (low randomness in head rotation) around a signalized T-junction. These findings based on on-road driving assessments provide credible evidence of performance overestimation by older drivers. Furthermore, the results suggest that making older drivers recognize the evaluative criteria might be effective for reducing the discrepancy between self-assessments and expert assessments. It was also suggested that improving the accuracy of one's self-assessment had the potential to improve driving behaviors such as choice of speed and scanning behavior.